Primary breast leiomyosarcoma: prognostic factors and treatment outcomes – a systematic review and case report (1969–2023) - Guo, Rui; Zhang, Weiwei; Ji, Xingli; Liu, Xiaohu; He, Lang (Frontiers in Oncology, 2025)
ObjectiveThis study aims to investigate the prognostic factors and treatment outcomes of primary breast leiomyosarcoma (PBL). We present a contemporary case of postoperative recurrence and metastasis, and conduct a systematic review to comprehensively analyze all reported cases over the past 54 years.MethodWe describe a 48-year-old female with primary breast leiomyosarcoma managed with multimodal therapy, including surgery, chemotherapy, radiotherapy, and immunotherapy. Additionally, a systematic review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines. We searched multiple electronic databases for studies on PBL published between 1969 and 2023. Patient demographics, clinical characteristics, and treatment strategies were extracted from the eligible studies. Kaplan-Meier survival analysis was employed to assess overall survival (OS), and Cox proportional hazards regression models were used to evaluate prognostic factors, including age, tumor size, and treatment approach.ResultThe systematic search identified 98 eligible studies, which collectively reported on 106 patients with PBL. The PRISMA 2020 flow diagram illustrated the study selection process. Among the patients, 86.8% were female, and 50.9% of tumors originated in the left breast. The mean pretreatment tumor diameter was 6.38 ± 4.98 cm. Surgical intervention was performed in 88.1% of cases, predominantly mastectomy. Survival analysis revealed a median OS of 18 months. Subgroup analysis demonstrated significantly shorter OS in patients aged ≤37 years at diagnosis or with tumors >7 cm (P<0.05). Multivariate Cox regression identified younger age at diagnosis as an independent predictor of poor prognosis (HR: 4.514, 95% CI: 1.146-17.784, P = 0.031).ConclusionSurgical resection remains the cornerstone of treatment for PBL. Our findings, derived from a PRISMA-guided systematic review, highlight younger age at diagnosis as a significant adverse prognostic factor, underscoring the need for tailored therapeutic strategies for this high-risk subgroup.